If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 12 + -4x + 4 = 40 Reorder the terms: 12 + 4 + 12x + -4x = 40 Combine like terms: 12 + 4 = 16 16 + 12x + -4x = 40 Combine like terms: 12x + -4x = 8x 16 + 8x = 40 Solving 16 + 8x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 8x = 40 + -16 Combine like terms: 16 + -16 = 0 0 + 8x = 40 + -16 8x = 40 + -16 Combine like terms: 40 + -16 = 24 8x = 24 Divide each side by '8'. x = 3 Simplifying x = 3
| b^2+30=11b | | X/8=76 | | 0.5(0.26+9x)=5.2x | | p^2-8p=-7 | | y=-5x^3-5x^2+60x | | 4/5g=1/4 | | mx/9=9 | | n^2=6-n | | -2.4x/-1.5= | | 5/7z=2/3 | | 13=x+13 | | 47=5w+12 | | 5(x+1)=2+x | | -382+9x=54x-23 | | x+y+z+a=12.68 | | 7x=-5x+2 | | 9883640/x=100/-0.6 | | 9883640/x=100-0.6 | | (1-x^3)(dy/dx))=3x^y | | -4=6+w | | -8x-2=10x-38 | | 3p=p+34 | | -x+6=-2x-32 | | 42u=252 | | f(x)=cotg(3-2x) | | 3q+6=q+14 | | 26=6x-8 | | 6y-14=16whatisy | | 6x+4y-2x+2y= | | 2-7/3=25 | | 14+3x=6x+133 | | 7(y+1)=3(2y-6) |